ЭЛЕКТРОННАЯ БИБЛИОТЕКА ГПНТБ СО РАН КАК ИНФОРМАЦИОННО-БИБЛИОТЕЧНАЯ СИСТЕМА НАУЧНЫХ РЕСУРСОВ И СЕРВИСОВ (Библиосфера)
The essence of the electronic library (EL) of SPSTL SB RAN as one of the models of scientific communications is revealed. The authors describe the main stages of EL development, which are characterized by qualitative changes in information and library service via electronic medium and diversification of its possibilities for users to work with different types of electronic resources. It is shown that now EL SPSTL SB RAN is a complicated information and library system, including not only all types of electronic resources, but also different forms of information and library services. Main groups of services in EL SPSTL SB RAN are described.